CHILD MARRIAGE IN THE RECIPROCITY CULTURE OF THE SEA TRIBE COMMUNITY: LEGAL CONFLICTS AND VIOLATIONS OF EDUCATION AND HEALTH RIGHTS - Tan, Winsherly; Budi, Henry Soelistyo; Shahrullah, Rina Shahriyani; Manashi Kalita (Faculty of Law, Parahyangan Catholic University, 2025)
The culture of “reciprocity” remains preserved and continues to serve as the foundation for the implementation of customary/Adat marriages among the indigenous Sea Tribe community in Lingga Regency. This study aims to strengthen cultural norms and regulatory frameworks, while also addressing the enforcement of such cultural practices. Employing an empirical legal approach, the study found that the practice of reciprocity conflicts with the prevailing national marriage law. Specifically, due to imbalances in social obligations, the Sea Tribe community often carries out child marriages based on custom without obtaining a court-issued marriage dispensation, as legally required. Furthermore, the Sea Tribe can no longer be classified as an Adat law community, as it no longer meets the criteria; instead, it should be regarded as a customary community that remains subject to national law. Drawing on Satjipto Rahardjo’s Theory of Legal Compliance, the study identifies three key factors contributing to the community’s non-compliance with marriage law: the lack of proper legal indoctrination, entrenched collective habits, and a limited understanding of the benefits of legal obedience. Consequently, the continued application of the reciprocity culture results in violations of children’s rights to health and education within the community. In light of Mochtar Kusumaatmadja’s Theory of Development Law, this study underscores the need for marriage law to more effectively govern the practices of the Sea Tribe community.